2009
DOI: 10.2223/jped.1953
|View full text |Cite
|
Sign up to set email alerts
|

Iron absorption from infant formula and iron-fortified cow’s milk: experimental model in weanling rats

Abstract: Objective: To compare iron absorption from infant formula and iron-fortified cow's milk.Methods: Twenty-four weanling Wistar rats were maintained in metabolic cages during the whole experiment (10 days). On the first day, the animals were divided into three similar groups according to their weight, length, hematocrit and hemoglobin levels: 1) infant formula; 2) powdered whole cow's milk fortified with iron in the same quantity and type as the formula; 3) control -powdered whole cow's milk not fortified with ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 21 publications
1
8
0
5
Order By: Relevance
“…The intention was to ensure that the animals had more than enough food available to meet their needs. Based on previous experience and nutritional content of the formulas, it was known that these volumes were sufficient, although this was confirmed during the experiment 28 . As the desire was to evaluate the absorption of minerals from the products analyzed, no adjustments for animal growth compared to rats fed an AIN-93G diet were made.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…The intention was to ensure that the animals had more than enough food available to meet their needs. Based on previous experience and nutritional content of the formulas, it was known that these volumes were sufficient, although this was confirmed during the experiment 28 . As the desire was to evaluate the absorption of minerals from the products analyzed, no adjustments for animal growth compared to rats fed an AIN-93G diet were made.…”
Section: Discussionmentioning
confidence: 79%
“…This experimental model allows us to evaluate the effects of a single fluid food, as occurs in the feeding of infants before the introduction of complementary foods. In this study, one group received a lactose-free cow's milk-based infant formula, as previous studies have found that weaned mice fed formula with higher amounts of lactose experienced loose stools, suggesting lactose intolerance 28 . Thus, a lactose-free reference product was used to compare to the soy-based infant formula.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations